Advanced glycation end-product pentosidine is not a relevant marker of disease activity in patients with rheumatoid arthritis - Senolt, L; Braun, M; Vencovský, J; Sedová, L; Pavelka, K (Physiological research, 2007)
Advanced glycation end-product (AGE) pentosidine has previously been demonstrated in different tissues and body fluids. It was suggested as a novel marker for evaluating the pathologic activity in rheumatoid arthritis (RA). In this study we analyzed the relation between pentosidine and markers of inflammation, cartilage turnover, immune response, and disease status of RA. Using HPLC, we analyzed pentosidine in serum and synovial fluid from 39 patients with RA and in serum from 38 healthy controls. Cartilage oligomeric matrix protein (COMP) and antibodies to CCP (anti-CCP) were measured by ELISA. Clinical disease status was assessed by Disease Activity Score 28 (DAS 28) and functional status by Health Assessment Questionnaire (HAQ). We demonstrated significantly higher serum levels of pentosidine in RA patients in comparison with controls. Pentosidine in serum significantly correlated with pentosidine in synovial fluid. Serum pentosidine levels were associated with erythrocyte sedimentation rate (p<0.03) but not with CRP, COMP, anti-CCP antibodies, DAS 28, or HAQ. In contrast to previous studies, we could not show any correlation of pentosidine levels with inflammatory status, clinical disease activity, markers of immune response, or cartilage breakdown. However, AGEs can be suggested as important players participating in joint destruction rather than markers of disease activity.
Keywords: kloubní chrupavka; Chromatography, High Pressure Liquid; lysin; Humans; extracelulární matrix - proteiny; lidé středního věku; Lysine; Arthritis, Rheumatoid; Female; ELISA; Cartilage, Articular; Glycation End Products, Advanced; Inflammation; Matrilin Proteins; lidé; Biomarkers; zánět; Enzyme-Linked Immunosorbent Assay; Arginine; Cartilage Oligomeric Matrix Protein; Synovial Fluid; chrupavkový oligomerní matrixový protein; Extracellular Matrix Proteins; revmatoidní artritida; glykoproteiny; biologické markery; ženské pohlaví; Male; Glycoproteins; Middle Aged; arginin; produkty pokročilé glykace; matriliny; mužské pohlaví; synoviální tekutina; vysokoúčinná kapalinová chromatografie